PESANTREN, KYAI DAN TAREKAT (Potret Sejarah Pendidikan Islam di Indonesia) - Idrus L (fakultas Ushuluddin dan Dakwah IAIN Bone, 2020)
This article aims to understand the existence of pesantren (Islamic boarding school) in the history of Islamic education in Indonesia, the roles and linkages of kyai and tariqah in the traditional education system. The study found that pesantren are Islamic educational institutions that are culturally formed from the traditional, unique, and indigenous Indonesian culture. The success of Islamic teachings is inseparable from the role of kyai as an essential element for pesantren. The knowledge tariqah possessed by kyai, as a manifestation of the sufism teachings, is one aspect that characterizes the value system of ahl al-sunnah wa al-jama'ah embraced by pesantren. The connection is implemented in the form of existence of pesantren as a tariqah teaching media. On a small scale, the tarekat itself is used as a means of deed (amaliyah) in fostering the spirituality and morality of the students (santri) in pesantren. Keywords: Pesantren, Kyai, Tarekat, Islamic Education